The Ability To Analyze English Vowels In Films - Salmananda, Dandi; Siregar , Ayunda Putri Amirah; Lubis, Yani (CV. Generasi Insan Rafflesia, 2023)
Surabaya City Sukorilo District Early Childhood English Learning Since early childhood education, English has been used as a language of communication. This demand forces parents to compete to send their children to schools where English is the language of instruction. In Indonesia, learning English as a foreign language is starting to permeate early childhood education. Ages 0-6 are the golden years of life and a critical period that determines the development of the next child. All aspects of language use should be introduced to children before this golden age ends. AUD English began to be introduced at the kindergarten level. If you want to learn English, you need a proper learning method to improve it. Students' interest and desire to use English in a fun and engaging learning activity in a fluent, linguistic and social context. The purpose of this study is to acquire knowledge about early childhood education related to English learning at the kindergarten level in Sukolilo, Surabaya City. Data collection techniques were conducted through interviews. Direct oral information. Of the total 57 kindergartens in the Sucorillo region, 28 have become learning centers. According to the data obtained, as many as 28 people had experience teaching English in the course of teaching and learning at the kindergarten, which is the subject of the study.